Gathering Support for Green Tax Reform: Evidence from German Household Surveys - Rick van der Ploeg; Armon Rezai; Miguel Tovar (Center for Economic Studies and ifo Institute (CESifo), 2021)
Green tax reform is unpopular because, typically, the poor are hurt most by the higher prices of carbon-intensive commodities. If revenues from a carbon tax are recycled, it may be feasible to gain popular support for green tax reform. To investigate this, we estimate an EASI demand system from German household data and a labour supply schedule, using wage data, and the German income tax schedule and let emission intensities decline in the carbon tax. If the revenue from a carbon tax is recycled via a lump-sum transfer to all households, this gives more equitable albeit less efficient outcomes, yet 70% of households are worse off. If the revenue is recycled via lower income taxes, there is more efficiency at the expense of more inequality, and about half of households benefit. With a recycling mix of lump-sum transfers and lower income taxes, popular support can be mustered without hurting equity too much. We also investigate the effects of Germany meeting its legal target for curbing emissions by 55% in 2030 relative to 1990 levels. We find that most of emission reductions are due to producers responding by lowering emission intensities rather than by consumers to less carbon-intensive consumption categories.
Keywords: D12; D31; D62; D63; H23; J22; Q50; 330; popular support; carbon tax; revenue recycling; equity; EASI demand system; labour supply